Non-tubal ectopic pregnancy–case reports on diagnosis and management of ruptured primary abdominal ectopic and caesarean scar ectopic pregnancy in low resource setting - Ahorklo, Isaac M. K.; Nimoh-Brema, Nana A.; Attuah, Samuel K.; Wuobar, Francis (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Non-tubal ectopic pregnancy is a rare form of ectopic pregnancy with high morbidity and mortality. The diagnosis of non-tubal ectopic pregnancy requires a high index of suspicion. Clinical history, physical examination, and laboratory and ultrasonographic features may all be non-specific. Fortunately, a low threshold for diagnosis, urine and serum beta-human chorionic gonadotrophin (β-hCG) assays and transvaginal sonography allow earlier diagnosis. Consequently, both maternal survival rates and conservation of reproductive capacity are improved. We present 2 cases of non-tubal ectopic pregnancy. The first is a case of a 17-year-old female para 0+0 with a period of amenorrhea, who presented with lower abdominal pain and moderate bleeding per vaginam. A suspicion of a ruptured ectopic gestation was made and an emergency exploratory laparotomy done which revealed a ruptured ectopic gestation implanted on the lower edge of the omentum with intact tubes and ovaries bilaterally was seen intra op. The second case is a 32-year-old female gravida 4 para 2 + 1ectopic (2 previous caesarean section) who presented with recurrent bleeding per vaginam and lower abdominal pain. Transvaginal ultrasound (USG) report showed a cervical ectopic gestation and patient was counselled accordingly and prepared for curettage or total abdominal hysterectomy. However, about 18weeks gestation uterus, a gestation implanted in an old caesarean section scar extending into the cervix was seen intra op. No obvious intrauterine gestation, tubes and ovaries were all normal and hence a total abdominal hysterectomy was done with conservation of both ovaries. Non-tubal ectopic pregnancy is a rare but potentially life-threatening and often misdiagnosed condition. Our case presents an opportunity to discuss 2 different cases of rare forms of ectopic pregnancy and the importance of having a high index of suspicion to make a diagnosis and prompt management to reduce maternal morbidity and mortality.